2020
DOI: 10.1186/s12909-019-1914-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulated patient’s feedback to improve communication skills of clerkship students

Abstract: Background: The changing trends of the society and revisions to medical education have changed the way medical students are trained to adroitly care for patients hence, patient centered care has become need of today's society and communication skills are imperative in developing patient physician relationship. Increasingly, simulations are being used to aid medical students to incorporate theoretical knowledge into practice. There are innumerable studies regarding communication skills in terms of reliability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
(41 reference statements)
2
17
0
2
Order By: Relevance
“…SP feedback on communication skills was particularly appreciated by pharmacy students to understand how they made the patients feel. This is in line with literature, which reports that SP feedback increases learner satisfaction and their relational focus [ 29 , 30 ]. Peer feedback can be valuable, and the study identified the need to be familiar with classmates before this occurs [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…SP feedback on communication skills was particularly appreciated by pharmacy students to understand how they made the patients feel. This is in line with literature, which reports that SP feedback increases learner satisfaction and their relational focus [ 29 , 30 ]. Peer feedback can be valuable, and the study identified the need to be familiar with classmates before this occurs [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…We presented the most important factors influencing a good communication situation within the educational process and we presented in more detail the research that dealt with the real application of the theoretical basis of the communicative concept of teaching in selected humantin-oriented subjects. Currently, the issue of the communication concept (principle) in teaching enjoys considerable interest in scientific research (see for example Adebayo, 2020;Lo & Hsieh, 2020;Qureshi & Zehra, 2020;Yang, 2020) -this fact is completely understandable to global events. We believe that teaching will move in the direction of developing the skills and abilities of students (especially communication) at the expense of memorable acquisition of information.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Authentic scenarios in OSCE provide opportunities for assessment of student performance, and patient feedback on student performance can be valuable in improving student communication skills and can be used as a reliable learning tool. 4,21 Where patients are supported and trained appropriately, "they can teach and assess as reliably as doctors," and there may be no significant differences between using simulated and real patients. 8,22 Previous studies on medical students have also shown that SP ratings can have a reliable correlation with assessor ratings and, therefore, may be used formatively.…”
Section: Ta B L E 3 Assessment Domains and Scores Assessed By Simulat...mentioning
confidence: 99%
“…2,3 It is widely accepted that formative assessment activities and receiving feedback from patients (real or simulated) can improve clinicians' communication and that such patients will support learning in complementary domains to the clinician expert, especially enhancing the humanistic elements over the more observable checklist content. [4][5][6] Once the graduated healthcare student is in the workplace, it is likely that patients will be judging them on a daily basis, and to be fully prepared for practice perhaps this patient voice should be highlighted in their undergraduate studies. Patient involvement has been encouraged in contemporaneous medical education to reinforce patient-centred care and shared decision-making.…”
Section: Introductionmentioning
confidence: 99%